Sense of Nationalism as an Undercurrent in Muna-Madan - K.C., Chandra Bahadur (Journal of Development Review, 2022)
A nation-state exists, showing typical identity, by the expression of its nationalism. The expression of nationalism is found in a number of social, cultural, religious, ethnic, and literary activities and artefacts. National issues and identities are also reflected in various literary texts. Laxmi Prasad Devkota’s best-loved and liked folk narrative epic poem Muna-Madan is an imaginative piece of literature that mainly tells the snatching of newly sprouted love between just married couple Muna and Madan. But this research paper claims that the poem also reflects the national issues and identities that are relevant to express Nepali nationalism. The description of geographical and cultural features of Nepal in the text foreground the nationalistic feeling. Though being far away from the country physically, the protagonist Madan glorifies the nation by keeping it always in the mind’s eye. Madan shows his patriotic feeling by valorizing the Nepali race, caste, culture and custom. National consciousness is deep-rooted in him. The paper concludes with the conviction that Muna-Madan depicts the geography, customs and cultures of Nepal to express nationalism. It clearly certifies that the sense of nationalism is not only limited to territorial boundary; it crosses the trance-border line by reflecting in people’s minds.